Preparation method of hydrogel composite material for soil heavy metal adsorption

By using aminotriazine modified polyvinyl alcohol and quaternary ammonium benzaldehyde crosslinking agent in hydrogel materials, a hydrogel composite with high water absorption and mechanical strength is formed, which solves heavy metals in the soil The problem of poor ion adsorption effect has achieved efficient adsorption of chromium and cadmium, significantly improving the soil repair ability.

CN119119512AActive Publication Date: 2024-12-13AGRI INST OF AGRI JIANGXI PROVINCE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411147354.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing hydrogel materials have poor adsorption effect on heavy metal ions such as chromium and cadmium in the soil, making it difficult to effectively repair contaminated soil.

Method used

The cross-linking reaction is carried out by aminotriazine modified polyvinyl alcohol and quaternary ammonium benzaldehyde cross-linking agent to form a hydrogel composite material with a three-dimensional spatial network structure and a quaternary ammonium structure, and it is used to form coordination bonds with heavy metal ions. and electrostatic interaction for adsorption.

Benefits of technology

The hydrophilicity and mechanical strength of the hydrogel are significantly improved, and efficient adsorption of Cd2+ and Cr2O72- is achieved, with adsorption rates reaching 96.0% and 98.5% respectively, which are effectively used for soil repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119512A_ABST
    Figure CN119119512A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of soil remediation, and discloses a preparation method of a hydrogel composite material for soil heavy metal adsorption, a quaternary ammonium salt benzaldehyde cross-linking agent and amino groups of aminotriazine modified polyvinyl alcohol are subjected to a cross-linking reaction, and the hydrogel composite material with a triazine-Schiff base cross-linked structure is formed. The concrete has the advantages of high water absorption and good water-retaining property. The molecular chain of the hydrogel contains rigid benzene ring groups, so that a rigid chemical cross-linked network is formed, and the mechanical strength of the hydrogel can be improved. The hydrogel composite material contains a triazine-Schiff base structure, can form coordinate bonds with heavy metal ions such as cadmium, and adsorbs the heavy metal ions through chelation; in addition, the hydrogel composite material contains a quaternary ammonium salt cation structure, and can form electrostatic interaction with Cr2O7 < 2->, so that adsorption is carried out. As a soil remediation material, the hydrogel composite material has good application in the aspects of soil water retention, soil heavy metal adsorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil remediation, and in particular to a method for preparing a hydrogel composite material for soil heavy metal adsorption. Background Art

[0002] With the rapid development of mining, metallurgy, electroplating and other industries, a large amount of heavy metal wastes such as cadmium, lead and chromium will be generated. If these heavy metal wastes are not effectively treated and are randomly discarded in the natural environment, they will cause serious environmental pollution and cause serious harm to the growth and reproduction of animals and crops in the soil. In recent years, repairing the soil in the natural environment and reducing the heavy metal pollution in the soil have been research hotspots. Hydrogel materials have good hydrophilicity and water absorption, and are widely used in soil remediation and environmental protection fields; Patent CN108148208B discloses that wastewater containing hemicellulose is used as a solvent, mixed with hydrogel monomers and crosslinking agents to obtain crosslinked polymer hydrogels, which can be used as supplementary nutrition for crops and soil microorganisms, promote water retention in soil ecological improvers, and play a role in soil remediation, but the soil improvement hydrogel does not show adsorption effect on heavy metal ions such as chromium and cadmium in the soil. Summary of the invention

[0003] Technical problem to be solved: Provides a hydrogel composite material with high water absorption and water retention and high adsorption performance, which can be well used in soil heavy metal adsorption and soil remediation.

[0004] Technical solution:

[0005] A preparation method of a hydrogel composite material: water, aminotriazine-modified polyvinyl alcohol, quaternary ammonium salt benzaldehyde crosslinking agent, and ethanol are added to a flask equipped with a condenser reflux tube, stirred and reacted at a temperature of 80-95° C. for 3-8 hours, cooled to precipitate, filtered, washed with ethanol, the product was placed in a dialysis bag, and dialyzed with distilled water for purification to obtain a hydrogel composite material;

[0006] The chemical structure of the quaternary ammonium salt benzaldehyde cross-linking agent is:

[0007]

[0008] Furthermore, the mass of the quaternary ammonium salt benzaldehyde cross-linking agent is 4-15% of the mass of the aminotriazine modified polyvinyl alcohol.

[0009] Further, the volume of ethanol is 5-15% of the volume of water.

[0010] Furthermore, aminotriazine-modified polyvinyl alcohol is prepared according to the following method: N,N-dimethylformamide, polyvinyl alcohol and sodium hydride are added to a flask equipped with a condenser reflux tube, nitrogen is introduced, and the mixture is stirred at room temperature for 1-3 hours, and then 2-chloro-4,6-diamino-1,3,5-triazine is added, and the mixture is stirred at a temperature of 130-150° C. for 6-12 hours, cooled, and the solution is poured into water for precipitation, filtered, washed with water, and dried to obtain aminotriazine-modified polyvinyl alcohol.

[0011] Furthermore, the masses of sodium hydride and 2-chloro-4,6-diamino-1,3,5-triazine are (5-25)% and (12-50)% of the mass of polyvinyl alcohol, respectively.

[0012] Further, the quaternary ammonium salt benzaldehyde cross-linking agent is prepared according to the following method:

[0013] (1) Methanol, N,N-methylenebisacrylamide and N,N,N'-trimethylethylenediamine were added to a flask equipped with a condenser reflux tube, and the mixture was reacted at a temperature of 55-65° C. for 10-18 hours. The solvent was removed by concentration, and the product was recrystallized in ethanol to obtain intermediate A.

[0014] (2) Add acetonitrile, intermediate A, and 4-chloromethylbenzaldehyde to a flask equipped with a condenser reflux tube, concentrate the solvent after the reaction, and recrystallize the product in ethanol to obtain a quaternary ammonium salt benzaldehyde cross-linking agent.

[0015] Furthermore, the mass of 4-chloromethylbenzaldehyde in (2) is (180-230)% of the mass of intermediate A.

[0016] Furthermore, the reaction in (2) is carried out at a temperature of 70-80° C. for 24-48 hours.

[0017] Furthermore, the application of hydrogel composites in soil heavy metal adsorption.

[0018] Technical effect: The present invention uses sodium hydride as a catalyst to react polyvinyl alcohol with 2-chloro-4,6-diamino-1,3,5-triazine to obtain aminotriazine-modified polyvinyl alcohol; uses N,N-methylenebisacrylamide and N,N,N'-trimethylethylenediamine to carry out Michael addition reaction, and then carries out quaternization reaction with 4-chloromethylbenzaldehyde to obtain a quaternary ammonium salt benzaldehyde crosslinking agent, and then uses its multiple aldehyde groups to carry out crosslinking reaction with the amino group of aminotriazine-modified polyvinyl alcohol to form a triazine-Schiff base crosslinking structure. hydrogel composites.

[0019] The polyvinyl alcohol-based hydrogel composite material of the present invention has a chemically cross-linked three-dimensional spatial network structure, and the polyvinyl alcohol hydrogel molecular chain contains a hydrophilic quaternary ammonium salt structure, which significantly improves the hydrophilicity of the hydrogel and has the advantages of high water absorption and good water retention. In addition, the hydrogel molecular chain contains a rigid benzene ring group to form a rigid chemically cross-linked network, which is beneficial to improving the mechanical strength of the hydrogel.

[0020] The hydrogel composite material of the present invention contains a triazine-Schiff base structure It can form coordination bonds with heavy metal ions such as cadmium and adsorb heavy metal ions through chelation. 2+ The adsorption capacity of the hydrogel composite material reached up to 96.0%; and the hydrogel composite material contained a quaternary ammonium salt cation structure, which could 2- The electrostatic force is formed to adsorb Cr2O7 2- The adsorption rate can reach up to 98.5%. The hydrogel composite material can be used as a soil remediation material in soil water retention, soil heavy metal adsorption and other aspects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a reaction route for preparing a quaternary ammonium salt benzaldehyde crosslinking agent.

[0022] Figure 2 This is the reaction route for preparing aminotriazine-modified polyvinyl alcohol. DETAILED DESCRIPTION

[0023] In the following description, for the purpose of illustration, in order to provide a comprehensive understanding of one or more embodiments, many specific details are set forth. However, it is apparent that these embodiments may also be implemented without these specific details. In other examples, for ease of describing one or more embodiments, known structures and devices are shown in the form of block diagrams.

[0024] Example 1

[0025] Add 20 mL of methanol and 1.5 g of N,N-methylenebisacrylamide to a flask equipped with a condenser reflux tube. 2.2g N,N,N'-trimethylethylenediamine The reaction was carried out at 60°C for 10 h, the solvent was removed by concentration, and the product was recrystallized in ethanol to obtain intermediate A.

[0026] To a flask equipped with a condenser reflux tube, 40 mL of acetonitrile, 2 g of intermediate A, and 3.6 g of 4-chloromethylbenzaldehyde were added, and the mixture was reacted at 80° C. for 36 h. The solvent was concentrated, and the product was recrystallized in ethanol to obtain a quaternary ammonium salt benzaldehyde cross-linking agent.

[0027] To a flask equipped with a condenser reflux tube, add 250 mL of N,N-dimethylformamide, 20 g of polyvinyl alcohol, and 1 g of sodium hydride, introduce nitrogen, stir at room temperature for 1 hour, then add 2.4 g of 2-chloro-4,6-diamino-1,3,5-triazine, react at 130°C for 12 hours, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain aminotriazine-modified polyvinyl alcohol.

[0028] To a flask equipped with a condenser reflux tube, 800 mL of water, 30 g of aminotriazine-modified polyvinyl alcohol, 1.2 g of quaternary ammonium benzaldehyde crosslinker, and 40 mL of ethanol were added, and the mixture was stirred at 90°C for 8 h. The precipitate was cooled and filtered, washed with ethanol, and the product was placed in a dialysis bag and purified by dialyzing with distilled water to obtain a hydrogel composite material.

[0029] Example 2

[0030] Add 15 mL of methanol, 1.5 g of N,N-methylenebisacrylamide, and 2.4 g of N,N,N'-trimethylethylenediamine to a flask equipped with a condenser reflux tube, react at 65°C for 10 h, concentrate to remove the solvent, and recrystallize the product in ethanol to obtain intermediate A.

[0031] To a flask equipped with a condenser reflux tube, 60 mL of acetonitrile, 2 g of intermediate A, and 4.2 g of 4-chloromethylbenzaldehyde were added, and the mixture was reacted at 75° C. for 48 h. The solvent was concentrated, and the product was recrystallized in ethanol to obtain a quaternary ammonium salt benzaldehyde cross-linking agent.

[0032] To a flask equipped with a condenser reflux tube, add 300 mL of N,N-dimethylformamide, 20 g of polyvinyl alcohol, and 2 g of sodium hydride, introduce nitrogen, stir at room temperature for 2 h, then add 4.5 g of 2-chloro-4,6-diamino-1,3,5-triazine, react at 130 ° C for 12 h, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain aminotriazine-modified polyvinyl alcohol.

[0033] To a flask equipped with a condenser reflux tube, 800 mL of water, 30 g of aminotriazine-modified polyvinyl alcohol, 2 g of quaternary ammonium benzaldehyde crosslinker, and 60 mL of ethanol were added, and the reaction was stirred at 95°C for 3 h. The precipitate was cooled and filtered, washed with ethanol, and the product was placed in a dialysis bag and purified by dialyzing with distilled water to obtain a hydrogel composite material.

[0034] Example 3

[0035] Add 20 mL of methanol, 1.5 g of N,N-methylenebisacrylamide, and 2.4 g of N,N,N'-trimethylethylenediamine to a flask equipped with a condenser reflux tube, react at 55°C for 18 h, concentrate to remove the solvent, and recrystallize the product in ethanol to obtain intermediate A.

[0036] To a flask equipped with a condenser reflux tube, 60 mL of acetonitrile, 2 g of intermediate A, and 4.6 g of 4-chloromethylbenzaldehyde were added, and the mixture was reacted at 70° C. for 48 h. The solvent was concentrated, and the product was recrystallized in ethanol to obtain a quaternary ammonium salt benzaldehyde cross-linking agent.

[0037] To a flask equipped with a condenser reflux tube, add 400 mL of N,N-dimethylformamide, 20 g of polyvinyl alcohol, and 3.5 g of sodium hydride, introduce nitrogen, stir at room temperature for 2 h, then add 8 g of 2-chloro-4,6-diamino-1,3,5-triazine, react at 150 ° C for 6 h, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain aminotriazine-modified polyvinyl alcohol.

[0038] To a flask equipped with a condenser reflux tube, 800 mL of water, 30 g of aminotriazine-modified polyvinyl alcohol, 3.2 g of quaternary ammonium benzaldehyde crosslinker, and 80 mL of ethanol were added, and the reaction was stirred at 95°C for 6 h. The precipitate was cooled and filtered, washed with ethanol, and the product was placed in a dialysis bag and dialyzed with distilled water to obtain a hydrogel composite material.

[0039] Example 4

[0040] Add 20 mL of methanol, 1.5 g of N,N-methylenebisacrylamide, and 2.2 g of N,N,N'-trimethylethylenediamine to a flask equipped with a condenser reflux tube, react at 65°C for 10 h, concentrate to remove the solvent, and recrystallize the product in ethanol to obtain intermediate A.

[0041] To a flask equipped with a condenser reflux tube, 40 mL of acetonitrile, 2 g of intermediate A, and 3.6 g of 4-chloromethylbenzaldehyde were added, and the mixture was reacted at 75° C. for 24 h. The solvent was concentrated, and the product was recrystallized in ethanol to obtain a quaternary ammonium salt benzaldehyde cross-linking agent.

[0042] To a flask equipped with a condenser reflux tube, add 400 mL of N,N-dimethylformamide, 20 g of polyvinyl alcohol, and 5 g of sodium hydride, introduce nitrogen, stir at room temperature for 3 h, then add 10 g of 2-chloro-4,6-diamino-1,3,5-triazine, react at 150 ° C for 10 h, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain aminotriazine-modified polyvinyl alcohol.

[0043] To a flask equipped with a condenser reflux tube, 800 mL of water, 30 g of aminotriazine-modified polyvinyl alcohol, 4.5 g of quaternary ammonium benzaldehyde crosslinking agent, and 120 mL of ethanol were added, and the reaction was stirred at 80°C for 8 h. The precipitate was cooled and filtered, washed with ethanol, and the product was placed in a dialysis bag and dialyzed with distilled water to obtain a hydrogel composite material.

[0044] Comparative Example 1

[0045] The difference between Comparative Example 1 and Example 1 is that no quaternary ammonium salt benzaldehyde crosslinking agent is used to crosslink the aminotriazine-modified polyvinyl alcohol.

[0046] Add 800 mL of water and 30 g of aminotriazine-modified polyvinyl alcohol into a flask equipped with a condenser reflux tube, stir and dissolve at 90°C, cool to 60°C, stand and degas, freeze the solution in a freezer at -25°C for 12 h, then thaw at room temperature for 6 h, repeat the freeze-thaw process 3 times to obtain a hydrogel composite material.

[0047] Comparative Example 2

[0048] The difference between Comparative Example 2 and Example 1 is that an equal mass of glutaraldehyde is used to replace the quaternary ammonium salt benzaldehyde cross-linking agent to cross-link the aminotriazine-modified polyvinyl alcohol.

[0049] To a flask equipped with a condenser reflux tube, 800 mL of water, 30 g of aminotriazine-modified polyvinyl alcohol, 1.2 g of glutaraldehyde, and 40 mL of ethanol were added, and the reaction was stirred at 90°C for 8 h. The precipitate was cooled and filtered, washed with ethanol, and the product was placed in a dialysis bag and purified by dialyzing with distilled water to obtain a hydrogel composite material.

[0050] Determination of water absorption rate of hydrogel composite material: Weigh a certain mass (m) of hydrogel composite material, put it into distilled water, soak it at room temperature for 6 hours, take out the hydrogel, wipe off the excess water, and weigh it m1; calculate the water absorption rate Q. Place the hydrogel after water absorption at room temperature for 168 hours, then wipe off the excess water, weigh it m2; calculate the water retention rate W. Water absorption rate Q = (m1-m) / m; Water retention rate W = (m2 / m1)×100%.

[0051] Table 1 Water absorption and water retention test of hydrogel composites

[0052] Water absorption (g / g) Water retention rate (%) Example 1 31.4 91.1 Example 2 60.9 83.9 Example 3 56.4 81.6 Comparative Example 4 39.8 88.7 Comparative Example 1 2.9 39.6 Comparative Example 2 8.6 72.1

[0053] In Examples 1-4, a quaternary ammonium benzaldehyde crosslinking agent is used to carry out a crosslinking reaction with the amino group of aminotriazine-modified polyvinyl alcohol to obtain a polyvinyl alcohol-based hydrogel composite material having a chemically crosslinked three-dimensional spatial network structure. At the same time, the polyvinyl alcohol hydrogel molecular chain contains a hydrophilic quaternary ammonium salt structure, which significantly improves the hydrophilicity of the hydrogel and has the advantages of high water absorption and good water retention.

[0054] Comparative Example 1 adopts the freeze-thaw method to prepare the polyvinyl alcohol-based hydrogel composite material, which does not contain a hydrophilic quaternary ammonium salt structure and does not form a chemically cross-linked three-dimensional spatial network structure, and has poor water absorption and water retention.

[0055] In Comparative Example 2, glutaraldehyde is used instead of the quaternary ammonium salt benzaldehyde crosslinking agent to crosslink the aminotriazine-modified polyvinyl alcohol, which does not contain a hydrophilic quaternary ammonium salt structure, and the water absorption rate and water retention of the hydrogel composite material are poor.

[0056] The tensile strength of hydrogel composites was tested according to the method of GB / T1040.1-2006

[0057] Table 2 Water absorption and water retention test of hydrogel composites

[0058] Tensile strength(MPa) Example 1 0.51 Example 2 0.59 Example 3 0.72 Comparative Example 4 0.66 Comparative Example 1 0.19 Comparative Example 2 0.37

[0059] In Example 1-4, a quaternary ammonium salt benzaldehyde crosslinking agent is used to carry out a crosslinking reaction with the amino group of aminotriazine-modified polyvinyl alcohol. The hydrogel molecular chain contains a rigid benzene ring group to form a rigid chemical crosslinking network, which is beneficial to improving the mechanical strength of the hydrogel.

[0060] Comparative Example 1 adopts the freeze-thaw method to obtain a polyvinyl alcohol-based hydrogel composite material, which does not form a rigid chemical cross-linking network and has the lowest tensile strength.

[0061] The hydrogel molecular chain of Comparative Example 2 does not contain a rigid benzene ring group, and the tensile strength of the hydrogel is poor.

[0062] Soil metal ion adsorption simulation experiment: Weigh 100g natural soil, crush and dry it, mix it with 10mg cadmium nitrate or potassium dichromate, add it to 400mL water, stir it thoroughly to make a simulated soil solution, remove the last clear solution, and measure the Cd content of the simulated soil solution by atomic absorption spectrophotometry. 2+ or Pb 2+ Add 0.3g of hydrogel composite material, stir and adsorb for 4h, and measure the Cd in the solution 2+ or Pb 2+ The concentration C1 is used to calculate the adsorption rate A. A = (C-C1) / C×100%. C is the concentration of metal ions in the soil solution before adsorption, and C1 is the concentration of metal ions in the soil solution after adsorption.

[0063] Table 3. Test of adsorption performance of water-absorbent resin.

[0064]

[0065] The hydrogel composite material prepared in Example 1-4 contains a triazine-Schiff base structure It can form coordination bonds with heavy metal ions such as cadmium and adsorb heavy metal ions through chelation. 2+ The adsorption capacity of the hydrogel composite material reached up to 96.0%; and the hydrogel composite material contained a quaternary ammonium salt cation structure, which could 2-The electrostatic force is formed to adsorb Cr2O7 2- The adsorption rate can reach up to 98.5%.

[0066] The hydrogel composite material of Comparative Example 1 does not contain a triazine-Schiff base structure and a quaternary ammonium salt cation structure. 2+、 Cr2O7 2- The chelation and electrostatic interactions are low, and the adsorption performance is poor.

[0067] The hydrogel composite material of Comparative Example 2 does not contain a quaternary ammonium salt cation structure, and the Cr2O7 2- The electrostatic interaction is low and the adsorption performance is poor.

Claims

1. A method for preparing a hydrogel composite material, It is characterized in that The hydrogel composite material is prepared according to the following method: water, aminotriazine-modified polyvinyl alcohol, quaternary ammonium salt benzaldehyde crosslinking agent, and ethanol are added to a flask equipped with a condenser reflux tube, stirred and reacted at a temperature of 80-95° C. for 3-8 hours, cooled to precipitate, filtered, washed, and the product was placed in a dialysis bag, dialyzed with distilled water for purification to obtain a hydrogel composite material; The chemical structure of the quaternary ammonium salt benzaldehyde cross-linking agent is:

2. The method for preparing the hydrogel composite material according to claim 1, It is characterized in that The mass of the quaternary ammonium salt benzaldehyde cross-linking agent is 4-15% of the mass of the aminotriazine modified polyvinyl alcohol.

3. The method for preparing the hydrogel composite material according to claim 1, It is characterized in that The volume of ethanol is 5-15% of the volume of water.

4. The method for preparing the hydrogel composite material according to claim 1, It is characterized in that The aminotriazine-modified polyvinyl alcohol is prepared according to the following method: N,N-dimethylformamide, polyvinyl alcohol and sodium hydride are added to a flask equipped with a condenser reflux tube, nitrogen is introduced, and the mixture is stirred at room temperature for 1-3 hours, and then 2-chloro-4,6-diamino-1,3,5-triazine is added. After the reaction, the mixture is cooled, and the solution is poured into water for precipitation, filtered, washed, and dried to obtain the aminotriazine-modified polyvinyl alcohol.

5. The method for preparing the hydrogel composite material according to claim 4, It is characterized in that The masses of the sodium hydride and 2-chloro-4,6-diamino-1,3,5-triazine are respectively (5-25)% and (12-50)% of the mass of the polyvinyl alcohol.

6. The method for preparing the hydrogel composite material according to claim 4, It is characterized in that The reaction is carried out at a temperature of 130-150°C for 6-12 hours.

7. The method for preparing the hydrogel composite material according to claim 1, It is characterized in that The quaternary ammonium salt benzaldehyde cross-linking agent is prepared as follows: (1) Add methanol, N,N-methylenebisacrylamide, and N,N,N'-trimethylethylenediamine to a flask equipped with a condenser reflux tube, react at a temperature of 55-65° C. for 10-18 hours, concentrate to remove the solvent, and recrystallize the product to obtain intermediate A; (2) Add acetonitrile, intermediate A, and 4-chloromethylbenzaldehyde to a flask equipped with a condenser reflux tube, concentrate the solvent after the reaction, and recrystallize the product to obtain a quaternary ammonium salt benzaldehyde cross-linking agent.

8. The method for preparing the hydrogel composite material according to claim 7, It is characterized in that The mass of 4-chloromethylbenzaldehyde in (2) is (180-230)% of the mass of intermediate A.

9. The method for preparing the hydrogel composite material according to claim 7, It is characterized in that The reaction in (2) is carried out at a temperature of 70-80° C. for 24-48 hours.

10. Use of the hydrogel composite material obtained by the preparation method according to any one of claims 1 to 9 in the adsorption of heavy metals in soil.

Citation Information

Patent Citations

  • Polyvinyl alcohol dichloro s-triazine crosslinking agent and synthesis method of the same

    CN101130578A

  • Copolymer temperature-sensitive hydrogel with high mechanical properties and preparation method thereof

    CN112048078A

  • Three-dimensional network bionic hydrogel as well as preparation method and application thereof

    CN112898599A

  • Cascade enzyme catalytic cross-linked natural polysaccharide hydrogel as well as preparation method and application thereof

    CN115403788A

  • Preparation method and application of soil conditioner

    CN117624465A